2017
DOI: 10.1155/2017/1287289
|View full text |Cite
|
Sign up to set email alerts
|

Expression of uPAR in Urinary Podocytes of Patients with Fabry Disease

Abstract: Background. Despite enzyme replacement therapy, Fabry nephropathy still progresses. Podocyturia is an irreversible event that antedates proteinuria and leads to chronic renal failure. We evaluated a potential mechanism of podocyte detachment via the expression of the urokinase-type Plasminogen Activator Receptor (uPAR) in urinary podocytes of Fabry patients. Methods. This is a cross-sectional study that included controls (n = 20) and Fabry patients (n = 44) either untreated (n = 23) or treated with agalsidase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 31 publications
(55 reference statements)
1
24
0
2
Order By: Relevance
“…In the case of IgA nephropathy, the number of uPAR + detached podocyte is significantly higher than controls and in patients with glomerular sclerotic lesions compared to those without (M1E0S1T0 vs M1E0S0T0 according to Oxford classification)[ 24 ]. Moreover, by western blot analysis as well as by PCR techniques we have confirmed the presence of elevated concentrations of uPAR in Fabry podocytes[ 23 ]. In this disease, we have found that urinary uPAR + podocytes are significantly higher in those without therapy[ 23 ].…”
Section: Mechanisms Of Podocyte Detachmentmentioning
confidence: 75%
See 3 more Smart Citations
“…In the case of IgA nephropathy, the number of uPAR + detached podocyte is significantly higher than controls and in patients with glomerular sclerotic lesions compared to those without (M1E0S1T0 vs M1E0S0T0 according to Oxford classification)[ 24 ]. Moreover, by western blot analysis as well as by PCR techniques we have confirmed the presence of elevated concentrations of uPAR in Fabry podocytes[ 23 ]. In this disease, we have found that urinary uPAR + podocytes are significantly higher in those without therapy[ 23 ].…”
Section: Mechanisms Of Podocyte Detachmentmentioning
confidence: 75%
“…Moreover, by western blot analysis as well as by PCR techniques we have confirmed the presence of elevated concentrations of uPAR in Fabry podocytes[ 23 ]. In this disease, we have found that urinary uPAR + podocytes are significantly higher in those without therapy[ 23 ]. Finally, in Fabry subjects increased levels of urinary αVβ3-integrins have been encountered[ 25 ].…”
Section: Mechanisms Of Podocyte Detachmentmentioning
confidence: 75%
See 2 more Smart Citations
“…La biopsia renal es importante, dado que conoce determinar el daño estructural renal, al realizarla es necesario utilizar tinción de hematoxilina-eosina y azul de toluidina en el estudio de microscopia de luz y se recomienda guardar una muestra de tejido en glutaraldehído para practicar microscopía electrónica, si está disponible, para evidenciar compromiso en los podocitos y puede tener impacto en el pronóstico y en la decisión terapéutica 9,[46][47][48] .…”
Section: Manifestaciones Renalesunclassified